Poderes locales y globales. Un estudio desde las evaluaciones de impacto ambiental en Las Toninas, partido de La Costa, Buenos Aires, Argentina - Verón, Eleonora Marta; Villar, María del Carmen (Geographicalia, 2014)
The new technologies of information and communication are the main material in the process of globalization, one of the greatest advances in the use of fiber optic cables. That is why in this article tries to address, from a geographical analysis of the issue of telecommunications and global environmental implications at the local level. Our overall purpose is to highlight the power relations being established between dissimilar power emanating from transnational corporations with those that may emerge in the local area. All this in the context of a peripheral country, paying attention to the treatment of environmental issues involved with the explosion of telecommunications projects materialized global scale within the locality of The Atlantic Toninas, Pdo. La Costa, Buenos Aires Province. The environmental focus of this look is tight to the critical analysis of Environmental Impact Assessments that emerge in this process. In the qualitativeinquiry were used multivariate techniques.